A Novel Variant of HOXA10 gene, Ser19Cys, among Patients with Endometriosis and its Relationship with the Severity of the Disease - Hutajulu, Pinda; Dasuki, Djaswadi; Sadewa, Ahmad Hamim; Utoro, Totok (Universitas Gadjah Mada, 2013)
Endometriosis is a gynecological disease associated with inherited genetic traits. HOXA10 gene whichis expressed in uterine plays an important role in the pathogenesis of endometriosis. The protein affects thedevelopment of pinopodes as a biomarker of endometrial receptivity in endometriosis.The aim of this study isto examine if there is a mutation or polymorphism within HOXA10 gene among patients with endometriosis.Thirty twopatients and 32 healthy women were recruited as subjects of this study. The exon 2 of HOXA10which covers most of coding region was amplifi ed using PCR. The presence of a mutation or polymorphismwas detected by direct seguencing. The distribution of genotype and allele was analyzed using Chi square test with p<0.05 is considered as signifi cantly different. A novel heterozygous variant within exon 2 of HOXA10 which substitute an adenine into thymine was detected at base position 55. This missense alteration changed amino acid serine to cystein (Ser19Cys). Interestingly, this variant was detected in 12 endometriosis cases (38%) but none in control. Patients carry HOXA10 Ser19Cys variant were associated with dismenorea and more frequent in stage I endometriosis. The role of this variant in the function of HOXA10 protein and frequency among Indonesians need to be clarifi ed. We found a novel heterozygous HOXA10 gene variant, Ser19Cys.The genotype frequency is 38% among endometriosis patients but none in control. This variant found in patient with dismenore and endometriosis stage 1.Key words: HOXA10 gene, endometriosis, Ser19Cys polymophism